2011
DOI: 10.1080/0075417x.2011.614749
|View full text |Cite
|
Sign up to set email alerts
|

Interaction structures between a child and two therapists in the psychodynamic treatment of a child with Asperger's disorder

Abstract: Leading the charge to link intervention research with clinical practice is the development of process research, which involves a detailed analysis of specific therapeutic processes over the course of treatment. The delineation of interaction structures -repetitive patterns of interactions between patient and therapist over the course of treatment -can inform therapists of what may be expected from patients with particular patterns of symptoms or behaviours in their clinical practice and how interactions change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 17 publications
3
50
0
14
Order By: Relevance
“…Some are indicative of a clearly positive transferencecountertransference matrix, such as IS 1, while others denote a negative transference-countertransference matrix, such as ISs 3 and 4. These fi ndings are similar to those of other studies of ISs in child psychodynamic therapy, which also identifi ed positive and negative transferencecountertransference matrices (Goodman, 2015;Goodman & Athey-Lloyd, 2011;Ramires et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Some are indicative of a clearly positive transferencecountertransference matrix, such as IS 1, while others denote a negative transference-countertransference matrix, such as ISs 3 and 4. These fi ndings are similar to those of other studies of ISs in child psychodynamic therapy, which also identifi ed positive and negative transferencecountertransference matrices (Goodman, 2015;Goodman & Athey-Lloyd, 2011;Ramires et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Goodman (2015) and Goodman and Athey-Lloyd (2011) showed that the therapist contributes to interaction patterns. In their respective studies, they analyzed the sequential treatment of a child by two different therapists and found that each therapist made an independent contribution to the conformation of these structures, the magnitude of which differed between therapists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O CPQ tem sido utilizado em estudos desenvolvidos nos Estados Unidos e Inglaterra, visando explorar em profundidade a natureza do processo terapêutico e sua relação com o resultado (Schneider, Midgley, & Duncan, 2010;Schneider et al, 2009), a elaboração de protótipos da psicoterapia de crianças (Goodman, Midgley, & Schneider, 2016) e a identificação e análise das estruturas de interação no processo terapêutico (Goodman & Athey-Lloyd, 2011). As análises qualitativas e quantitativas possibilitadas pelo procedimento assim como a investigação do processo ao longo do tempo no interior de cada psicoterapia e entre diferentes tratamentos são recursos que oferecem importantes e inéditos vértices de observação.…”
unclassified